Information asymmetry, government ownership, and dividends from the building construction from Indonesia - Musdalifah Azis; Amalia, Siti; Caisar Darma, Dio (Social Development and Security, 2020)
This study investigated to examine the relationship between information asymmetry and government ownership to dividend policy. Information asymmetry is measured using bid-ask spreads, while government ownership is measured using the number of government shares divided by the number of outstanding shares multiplied by 100 %. This study uses purposive sampling with a total sample of 9 sub-companies construction and building listed on the Indonesia Stock Exchange (ISE) in 2016-2019. The data used is quantitative data and data sources were taken from the company’s annual financial statements. Descriptive statistics and panel data regression are used as data analysis tools. The results showed that information asymmetry has a positive and significant effect on dividend policy, government ownership does not have a significant negative effect on dividend policy, and the interaction of information asymmetry and government ownership moderates the dividend policy.